2020
DOI: 10.3390/catal10080876
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Designed Immobilized Catalytic Systems: Activity Enhancement of Lipase B from Candida antarctica

Abstract: Immobilized enzymatic catalysts are widely used in the chemical and pharmaceutical industries. As Candida antarctica lipase B (CALB) is one of the more commonly used biocatalysts, we attempted to design an optimal lipase-catalytic system. In order to do that, we investigated the enantioselectivity and lipolytic activity of CALB immobilized on 12 different supports. Immobilization of lipase on IB-D152 allowed us to achieve hyperactivation (178%) in lipolytic activity tests. Moreover, the conversion in enantiose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 71 publications
0
29
0
Order By: Relevance
“…Furthermore, in the case of immobilized enzymes, besides the support nature and structure, the reaction media strongly influenced the enzyme interaction with the inert support, modifying their catalytic properties, as recently presented by Siodmiak. 71 Four polar aprotic and nonpolar solvents were used in the study considering the biocatalyst stability. Based on our recent study, when n -hexane was found as the optimal solvent for the EKR of some racemic heteroaryl-ethanols mediated by CaL-B immobilized on chitosan–magnetic nanoparticles, 16 the stability of this new bioconjugate containing chitosan and the same enzyme in various solvents (dichloromethane – DCM, tetrahydrofuran – THF, chloroform and n -hexane) was further studied (see section 2.3.1).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in the case of immobilized enzymes, besides the support nature and structure, the reaction media strongly influenced the enzyme interaction with the inert support, modifying their catalytic properties, as recently presented by Siodmiak. 71 Four polar aprotic and nonpolar solvents were used in the study considering the biocatalyst stability. Based on our recent study, when n -hexane was found as the optimal solvent for the EKR of some racemic heteroaryl-ethanols mediated by CaL-B immobilized on chitosan–magnetic nanoparticles, 16 the stability of this new bioconjugate containing chitosan and the same enzyme in various solvents (dichloromethane – DCM, tetrahydrofuran – THF, chloroform and n -hexane) was further studied (see section 2.3.1).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, optimum temperature reported here were slightly different than previous studies. For example, at pH 7.4, an optimum temperature of 55˚C of for CalB was reported [58] while at pH 8.0, purified CalB demonstrated an optimum temperature of 52˚C [42].…”
Section: Plos Onementioning
confidence: 99%
“…CalB is expected to be a non-toxic and renewable energy source. It has the highest catalytic activity at neutral pH and 45 °C [ 12 , 13 , 14 ]. However, CalB is water soluble, which makes it highly sensitive to organic solvents, leading to reduced reaction efficiency [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%